Making Decisions About Purchases Based on Varying Consumer Behavior Concerning Product Quality Evaluations - Melia Wida Rahmayani; Abdul Hakim; Nita Hernita; Wulan Riyadi (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
The purpose of this study was to determine how consumer behavior and product quality influence purchasing decisions. The subject of this research is UD Putra TS Majalengka West Java, which is a company engaged in fashion in Majalengka. The analysis technique uses a bootstrapping resampling process to determine the hypothesis using SEM-PLS using a second-order approach. The results of this study indicate that consumer behavior and product quality are the two most important factors in influencing consumer choice.  Customer behavior significantly influences the final purchase decision, with cultural influences being the most influential force. Culture includes values, norms, beliefs, and practices that influence individuals and groups. Factors such as product preferences, communication styles, decision-making processes, and customer expectations influence customer behavior. To maintain profitability and market share, manufacturers must consider factors such as product quality, features, and price. Belief in product excellence increases the likelihood of purchase and can increase sales volume by maintaining quality and innovating. Measuring consumer behavior, product quality, and purchasing decisions is expected to use different indicators to be able to compare research results.